Brain atrophy and lesion load measures over 1 year relate to clinical status after 6 years in patients with clinically isolated syndromes. Issue 2 (10th September 2009) - Di Filippo, M; Anderson, V M; Altmann, D R; Swanton, J K; Plant, G T; Thompson, A J; Miller, D H
Abstract : Background: Conventional MRI lesion measures modestly predict long term disability in some clinically isolated syndrome (CIS) studies. Brain atrophy suggests neuroaxonal loss in multiple sclerosis (MS) with the potential to reflect disease progression to a greater extent than lesion measures. Objective: To investigate whether brain atrophy and lesion load, during the first year in patients presenting with CIS, independently predict clinical outcome (development of MS and disability at 6 years). Methods: 99 patients presenting with CIS were included in the study. T1 gadolinium enhanced and T2 weighted brain MRI was acquired at baseline and approximately 1 year later. Percentage brain atrophy rate between baseline and follow-up scans was analysed using SIENA. Results: Mean annual brain atrophy rates were −0.38% for all patients, −0.50% in patients who had developed MS at 6 years and −0.26% in those who had not. Brain atrophy rate (p = 0.005) and baseline T2 lesion load (p<0.001) were independent predictors of clinically definite MS. While brain atrophy rate was a predictor of Expanded Disability Status Scale (EDSS) score in a univariate analysis, only 1 year T2 lesion load change (p = 0.007) and baseline gadolinium enhancing lesion number (p = 0.03) were independent predictors of EDSS score at the 6 year follow-up. T1 lesion load was the only MRI parameter which predicted Multiple Sclerosis Functional Composite score at the 6 year follow-up. Conclusions: The findings confirm that brain atrophy occurs during the earliest phases of MS and suggest that 1 year longitudinal measures of MRI change, if considered together with baseline MRI variables, might help to predict clinical status 6 years after the first demyelinating event in CIS patients, better than measurements such as lesion or brain volumes on baseline MRI alone.